Transition towards a sustainable biobased economy - Morone, Piergiuseppe; Clark, James H. (RSC green chemistry series ;, 2020)
This book promotes the development of sustainability for the assessment of biobased products, which are fundamental to the establishment of a cutting-edge sustainable bioeconomy.